Contexto socioeducativo del estudiante en el proceso de aprendizaje - Yugsi Pilaguano, Yesenia Maribel (2023)
Education is a social process that allows the training of individuals to acquire learning that allows them to make their own decisions. The student's socio-educational context influences the learning process in a positive or negative way. This research was proposed with the objective of determining the socio-educational context of the students through narrative descriptions, for the understanding of the learning process of the students. A qualitative approach was used and information was collected on the qualities of the investigated subjects, through the applied interview technique triangulating informants (student, parent and tutor teacher). For the analysis of the data, the Atlas.ti software was used, which allowed the information to be processed through the creation of a hermeneutic unit made up of families of codes that came from deductive and inductive analysis. The results were presented through three dimensions: Social, External factors, Learning. Relating these dimensions, it was possible to observe that the social dimension (family composition, housing conditions, parents' level of study, household income), as well as external factors (health, nutrition) to which students are exposed They condition their learning process. Additionally, it was observed that students do not receive constant motivation from teachers, that they do not like to participate in classes and two students receive curricular adaptations in basic subjects.